Using inferior epigastric vascular anatomical landmarks for anterior inguinal hernia repair - Li, Weiming (BMC Surg, 2019)
BACKGROUND: Inferior epigastric vascular anatomical landmarks for anterior inguinal hernia repair is an alternative surgical procedure. We present our experience and outcome of the way. METHODS: We performed a retrospective analysis of 230 patients who received anterior tension-free hernia repair between May 2016 to May 2017. Among these cases, 120 were performed using the traditional transinguinal preperitoneal (TTIPP) technique while 100 were performed using the vascular anatomic landmark transinguinal preperitoneal (VALTIPP) technique. Between these two groups, we compared the operation time, length of hospital stay, complication rates, and the visual analog scale (VAS) for pain at 2 days, 3 months, and 6 months after surgery. RESULTS: Surgery was well-tolerated in both groups with no significant hemorrhage or complications. The operation times for the VALTIPP and TTIPP groups were 42.52 ± 9.15 and 53.84 ± 10.64 min (P < 0.05), respectively. Ten patients in the VALTIPP group and 17 patients in the TTIPP group reported sensations of foreign bodies (P < 0.05). The VAS pain score in VALTIPP patients at 2 days (4.0 ± 0.5), 3 months (1.0 ± 0.3), and 6 months (0.9 ± 0.3) were significantly lower when compared with those of TTIPP patients (5.3 ± 0.9 at 2 days, 1.8 ± 0.4 at 3 months, and 1.1 ± 0.1 at 6 months, p < 0.05). No statistically significant differences were found in age, gender, BMI, hernia type and location, follow-up period, incidence of post-operative seromas, recurrence rate, or length of hospital stay. CONCLUSION: Anterior inguinal hernia repair using inferior epigastric vascular anatomical landmarks may lead to reduced operation times, reduced sensations of foreign bodies, and reduced post-operative pain. This technique is simple, practical, and effective in the management of inguinal hernias.